Pancasila Democracy Between Concept and Practice: Is It Really Democracy? - Amanah, Arsifi (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
Democracy is a political system that is currently used by almost all nations and countries in the world. The democratic political system is not only used by liberal countries which uphold freedom, but it turns out that the democratic political system is also used by communist-minded countries which uphold togetherness or collectivity. Communist countries call the democracy they use proletarian democracy or people's democracy. In contrast to our country, Indonesia, which adheres to the Pancasila democratic political system, where the values contained in democracy must be based on Pancasila values. In Pancasila democracy, apart from being based on Pancasila values, there are 10 pillars of democracy mandated by the nation's founding fathers (founding fathers). Principles or joints are the main truths which are used as the basis for thoughts, actions and so on. Then in the Pancasila democratic government system there are seven main pillars which form the foundation.